Stem Cell-Based Therapies Combined With Nano-Biomaterials for Nerve Regeneration and Repair - Mittal, Vishnu; Sharma, Anjali; Goyal, Rajat; Wilson, Kashish; Hooda, Tanuj; Chopra, Shivani; Chopra, Hitesh (Scripta Medica, 2026)
Nerve injuries, often resulting from trauma or degenerative diseases, pose significant challenges due to limited regenerative capacity of nervous system. Conventional treatments, including surgical nerve grafts, exhibit limitations such as donor site morbidity and limited functional recovery. Emerging regenerative strategies combining stem cell-based therapies with nano-biomaterials offer promising solutions for enhancing nerve regeneration and functional restoration. A comprehensive review of recent advancements in stem cell sources and induced pluripotent stem cells (iPSCs) was discussed. Also design, properties and applications of nano-biomaterials such as nanoparticles, nanofibers and hydrogels in nerve repair were analysed. Preclinical and clinical studies demonstrating effectiveness of these combined strategies were evaluated. The integration of stem cells with nano-biomaterials has demonstrated improved nerve regeneration outcomes, including enhanced neuronal differentiation, reduced inflammation and accelerated axonal growth. Studies indicate that biomaterial scaffolds provide structural support and biochemical cues, facilitating stem cell survival and integration into damaged neural tissues. Stem cell-based therapies combined with nano-biomaterials represent a promising approach for nerve regeneration. This combinatorial strategy offers enhanced neuroprotection, functional recovery and long-term stability in neural repair. Future research should focus on optimising scaffold properties, improving cell survival rates and translating preclinical findings into clinical applications.